Building consumer confidence towards Internet banking: an analysis of corporate image factors - Torres Moraga, Eduardo; Flavián Blanco, Carlos; Hidalgo Campos, Pedro (Estudios de Administración, 2007)
Trust is one of the most important factors when selecting a particular financial institution, especially when it comes to adopting Internet banking. References to this in the relevant literature enable the notion to be put forward that the corporate image of a financial institution has a key role to play in increasing levels of trust among consumers. Given this viewpoint, and comparing Internet and conventional banking systems, the present study analyses how much consumer trust is influenced by each element that makes up the corporate image. The results of the analysis show that both security and the services offered have a stronger influence on trust regarding Internet banking as compared to conventional banking and that; on the contrary, reputation and accessibility to services are more favourable for building trust in the latter banking scenario. These results allow for banking directors to efficiently identify and manage corporate image factors that may have the strongest influence on consumers’ trust.